2005
DOI: 10.1111/j.1460-9568.2005.04211.x
|View full text |Cite
|
Sign up to set email alerts
|

Multisensory responses and receptive field properties of neurons in the substantia nigra and in the caudate nucleus

Abstract: The basal ganglia are widely regarded as structures involved in sensorimotor co-ordination, but little is known about the sensory background of their function. We publish here descriptions of the excitatory sensory responses and receptive field properties of the visual, auditory, somatosensory and multisensory caudate nucleus and substantia nigra pars reticulata neurons. Altogether 111 caudate nucleus and 124 substantia nigra sensory neurons were recorded in halothane-anaesthetized, immobilized, artificially v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 41 publications
4
40
0
Order By: Relevance
“…Although it is uncertain to which extent these divisions are applicable to the feline striatum, tracer experiments have depicted the basically similar organization (Malach and Graybiel, 1986;Norita et al, 1991;Updyke, 1993). The posterior caudate nucleus of the cat especially contains neurons that respond to different sensory stimuli such as visual, auditory, somatosensory or even multisensory inputs (Nagy et al, 2005). Importantly, all these neurons are confined to the dorsolateral sector of the posterior caudate, which closely matches the areas of high gap junctional coupling in this study.…”
Section: Implications In the Striatal Circuitrysupporting
confidence: 51%
“…Although it is uncertain to which extent these divisions are applicable to the feline striatum, tracer experiments have depicted the basically similar organization (Malach and Graybiel, 1986;Norita et al, 1991;Updyke, 1993). The posterior caudate nucleus of the cat especially contains neurons that respond to different sensory stimuli such as visual, auditory, somatosensory or even multisensory inputs (Nagy et al, 2005). Importantly, all these neurons are confined to the dorsolateral sector of the posterior caudate, which closely matches the areas of high gap junctional coupling in this study.…”
Section: Implications In the Striatal Circuitrysupporting
confidence: 51%
“…Additional t tests showed that quinpirole significantly decreased rCMR glc in LiCl diet but not in the control diet fed rats Significant baseline elevations in rCMR glc induced by the LiCl diet were found in central auditory (auditory cortex, habenular nucleus lateral, medial geniculate nucleus, and inferior colliculus) and visual (visual cortex, habenular nucleus medial, lateral geniculate nucleus, and superior colliculus) circuits (Brodal 1981). The pretectal area, which was affected, also can participate in visualoculomotor-auditory circuits (Clarke et al 2003), as can the other positively affected regions-hippocampus (Pollmann et al 2004), caudate-putamen (Arnauld et al 1996), and substantia nigra (Nagy et al 2005). Many of these regions belong to neural circuits that have been identified with functional and structural imaging, as important in modulating emotional behavior and as disturbed in mood disorders (Altshuler et al 2005;Carlson et al 2006;Chang et al 2004).…”
Section: Discussionmentioning
confidence: 97%
“…A large proportion of caudate neurons receives proprioceptive [15] and discriminative cutaneous sensory inputs [16, 17]. In monkeys, a microelectrode recording study reported that caudate neuronal response to sensory stimuli becomes less active after 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-treatment [18].…”
Section: Discussionmentioning
confidence: 99%